Pesticide exposure and sleep disorder: A cross-sectional study among Thai farmers - Chudchawal Juntarawijit; Uraiwan Chaichanawirote; Nootchayong Yaowapanon; Kajohnsak Noppakun (Heliyon)
Pesticide exposure might be an important risk factor for sleep disorders, however current epidemiological evidence is limited. The main objective of this study was to determine the association between historical use of pesticides and sleep disorders. Data on the historical use of 38 individual pesticides of almost thirty thousand Thai farmers were collected using questionnaire method. This information was linked to medically diagnosed sleep disorders using a multivariable logistic regression. The study found a positive association of 19 individual pesticides (twelve insecticides, two herbicides, and five fungicides). Some associations demonstrated a dose-response pattern. Additionally, the study revealed that women are at a higher risk of sleep-related issues with pesticide exposure compared to males. These results not only substantiate existing literature but also unveil several new individual pesticides that may impact sleep health. Sleep health should receive more attention, as it can contribute to various diseases and significantly impact the overall well-being of individuals.